Isothermal recombinase polymerase amplification-lateral flow detection of SARS-CoV-2, the etiological agent of COVID-19 - Shelite, Thomas R.; Uscanga-Palomeque, Ashanti C.; Castellanos-Gonzalez, Alejandro; Melby, Peter C.; Travi, Bruno L. (Journal of virological methods, 2021)
•Isothermal, rapid amplification and lateral flow qualitative detection of SARS-CoV-2.•Two-step, point-of-care diagnostic development for COVID-19.•Sensitive/specific assay that doesn’t require sophisticated equipment or training.•Able to detect 0.25–2.5 copies/μL of SARS-CoV-2 N gene containing plasmid.•SARS-CoV-2 detection from nasopharyngeal clinical samples. The rapid detection of novel pathogens including SARS-CoV-2 necessitates the development of easy-to-use diagnostic tests that can be readily adapted and utilized in both clinical laboratories and field settings. Delay in diagnosis has facilitated the rapid spread of this novel virus throughout the world resulting in global mortality that will surpass 2.5 million people. Development of point-of-care diagnostic assays that can be performed in rural or decentralized health care centers to expand testing capacity is needed. We developed a qualitative test based on recombinase-polymerase-amplification coupled with lateral flow reading (RPA-LF) for rapid detection of SARS-CoV-2. The RPA-LF detected SARS-CoV-2 with a limit of detection of 35.4 viral cDNA nucleocapsid (N) gene copies/μL. Additionally, the RPA-LF was able to detect 0.25–2.5 copies/μL of SARS-CoV-2 N gene containing plasmid. We evaluated 37 nasopharyngeal samples using CDC’s N3, N1 and N2 RT-real-time PCR assays for SARS-CoV-2 as reference test. We found a 100 % concordance between RPA-LF and RT-qPCR reference test as determined by 18/18 positive and 19/19 negative samples. All positive samples had Ct values between 19–37 by RT-qPCR. The RPA-LF primers and probe did not cross react with other relevant betacoronaviruses such as SARS and MERS. This is the first isothermal amplification test paired with lateral flow developed for qualitative detection of COVID-19 allowing rapid viral detection and with prospective applicability in resource limited and decentralized laboratories.